Post Hatch Histo-morphological Studies of Small Intestinal Development in Chicks Fed with Herbal Early Chick Nutritional Supplement - Yadav, G.B.; Kadam, A.S.; Pachpande, A.M.; Lambate, S.B.; Lonkar, V.D.; Maini , S.; Ravikanth, K. (International Journal of Poultry Science, 2010)
Earlier the food passes through gastrointestinal tract, better is the stimulus for initiating the gut function development. Morphology of the small intestine of Vencobb broiler chick was determined immediately post hatch by comparing between untreated control group fed with standard basal ration 48 h after hatch and the treatment groups (T2 and T3) offered Chikimune at 2 different doses of 6 and 8 g/chick/day for early 2 days followed by administration of standard basal ration after 2 days. Pattern of development of the intestinal mucosa, mechanisms underlying the structural changes in small intestine were assessed. The length, weight and diameter of different parts of small intestine developed significantly earlier in treatment groups (II and III) as compared to control (T1). Crypt depth and villous height increased with age in the duodenum, jejunum and illeum. There were also significant changes in apparent villous surface area in the three regions, while interactions between age and intestinal region were significant in the case of crypt depth and villous height although, the intestinal mucosa of the strain was structurally developed at hatch, there was much change in structure with age, especially over the first 7 day post hatch.